1986
DOI: 10.1073/pnas.83.23.9231
|View full text |Cite
|
Sign up to set email alerts
|

Continuous infusion of nerve growth factor prevents basal forebrain neuronal death after fimbria fornix transection.

Abstract: Neurons in the rat medial septum (MS) and vertical limb of the diagonal band of Broca (VDB) undergo a rapid and severe cell death after transection of their dorsal projection to the hippocampus by aspiration of the ipsilateral fimbria fornix and supracallosal striae. By 2 weeks posttransection, the extent of neuronal loss was 50% of the total neurons and 70% of the cholinergic neurons in the MS and 30% of the total neurons and 40% of the cholinergic neurons in the VDB.We hypothesized that (t) the death was due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
331
3
2

Year Published

1993
1993
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 820 publications
(359 citation statements)
references
References 53 publications
23
331
3
2
Order By: Relevance
“…Consistent with our results that NGF was not neurotrophic for cortical 5-HT axons are the findings that NGF fails to elicit 5-HT neurite outgrowth in embryonic raphe cultures , or cause serotonergic axon sprouting in the adult rat striatum (Kawaja and Gage, 1991), despite its ability to promote robust sprouting of cholinergic (Williams et al, 1986;Kawaja and Gage, 1991) and sympathetic (Isaacson et al, 1992) fibers. Moreover, NT-3, in this study, was considerably less potent than BDNF in promoting the survival of serotonergic axons after PCA, which remarkably parallels the relative potencies of these neurotrophins in augmenting 5-HT metabolism and analgesia (Siuciak et al, 1994).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Consistent with our results that NGF was not neurotrophic for cortical 5-HT axons are the findings that NGF fails to elicit 5-HT neurite outgrowth in embryonic raphe cultures , or cause serotonergic axon sprouting in the adult rat striatum (Kawaja and Gage, 1991), despite its ability to promote robust sprouting of cholinergic (Williams et al, 1986;Kawaja and Gage, 1991) and sympathetic (Isaacson et al, 1992) fibers. Moreover, NT-3, in this study, was considerably less potent than BDNF in promoting the survival of serotonergic axons after PCA, which remarkably parallels the relative potencies of these neurotrophins in augmenting 5-HT metabolism and analgesia (Siuciak et al, 1994).…”
Section: Discussionsupporting
confidence: 79%
“…Based on the findings from other neurodegeneration models, a tropic role for the neurotrophins in promoting axonal growth after injury has been proposed, in addition to their role in supporting neuronal survival (reviewed by Gage et al, 1990). For example, after fimbria-fornix transection, exogenous administration of NGF causes sprouting of local cholinergic axons in the lateral septum (Williams et al, 1986) and promotes the regrowth of lesioned septal cholinergic fibers across a "grafting bridge" into the hippocampus (Hagg et al, 1990;Tuszynski et al, 1990). In addition to its effects upon axotomized neurons, NGF can elicit the sprouting of mature, uninjured sympathetic axons (Isaacson et al, 1992) and promote neurite growth from nonlesioned cholinergic neurons in the adult brain (Koliatsos et al, 1991;Tuszynski et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, BDNF is also involved in the development of motor coordination (Strand et al, 2007). Several studies have demonstrated that age-and AD-related dysfunctions of the cholinergic system related to physical activity as well as cognitive function are ameliorated by NGF and BDNF treatment (Williams et al, 1986;Casamenti et al, 1994;Kordower et al, 1994;Murray et al, 1994).…”
mentioning
confidence: 99%
“…Neurotrophic molecules promote neuronal survival when exogenously administered in amounts that exceed normal physiological levels. NGF, the best-characterized member of the neurotrophin family, has been extensively studied for its role in the cholinergic septohippocampal model, where administration of exogenous NGF to the axotomized septohippocampal projection rescues up to 90% of the transected septal cholinergic neurons (Hefti, 1986;Williams et al, 1986;Kromer, 1987;Gage et al, 1988). A decrease in neurotrophic factors during aging has also been hypothesized to predicate degenerative disorders such as Alzheimer's disease (AD) and Parkinson's disease (PD; Appel, 1981;Hefti, 1983), where the loss of dopaminergic neurons of the substantia nigra pars compacta (SNC) is correlated with the major motor disability of PD, and the loss of cholinergic neurons in the basal forebrain is associated with memory loss in AD (Bernheimer et al, 1973;Olton, 1990).…”
Section: Indexing Termsmentioning
confidence: 99%